The molecular mechanism of ovary development in Thamnaconus septentrionalis induced by rising temperature via transcriptomics and metabolomics analysis - Liu, Yan; Xu, Wengang; Zhang, Xueli; Wang, Jiulong; Chen, Xiaoling; Yu, Xiaoyan; Zeng, Jun; Wu, Yanqing; Liu, Liming (Frontiers in Marine Science, 2025)
The greenfin horse-faced filefish, Thamnaconus septentrionalis, which is widely distributed in the Indo-West Pacific Ocean, is an important commercial fish species with characteristic blue-green fins, rough skin, and a spine-like first dorsal fin. Recently, T. septentrionalis has captured the attention of conservation and development due to its sharply declining population, and its great economic value as an important marine aquaculture fish species. To protect the resources of T. septentrionalis and develop its fishery industry, artificial breeding is essential and has been carried out gradually in local farms in China. A previous study has shown that temperature can effectively influence the gonadal development in T. septentrionalis in its overwintering state. However, the molecular mechanisms underlying the effects of temperature on the gonadal development in T. septentrionalis are still unrevealed and worth further study. In the present study, we systematically investigated the effects of temperature on ovary development in T. septentrionalis through transcriptomics and metabolomics analysis. The results showed that temperature rises significantly regulated the metabolic status of T. septentrionalis and promoted ovary development and maturation process through the regulation of the pathways of ECM-receptor interaction, regulation of actin cytoskeleton, oocyte meiosis, steroid hormone biosynthesis, lipid metabolism, ABC transporters, protein digestion and absorption, biosynthesis of amino acids pathways, etc. The histological, scanning electron microscope, and transmission electron microscope analyses showed that the oocytes in the ovaries of T. septentrionalis experiencing the temperature rises developed from phase II to III with increased gonadal somatic index and 17β-estradiol level. The present study for the first time elucidated the potential molecular regulatory mechanism of ovary development in T. septentrionalis induced by temperature and will provide valuable information for the artificial breeding of T. septentrionalis and conservation of T. septentrionalis fishery resources in the future.